Shipwreck Modernity : Ecologies of Globalization, 1550-1719 - Mentz, Steve (Book collections on Project MUSE., 2015)
This title engages early modern representations of maritime disaster in order to describe the global experience of ecological crisis. In the wet chaos of catastrophe, sailors sought temporary security as their worlds were turned upside down. Similarly, writers, poets, and other thinkers searched for stability amid the cultural shifts that resulted from global expansion. The ancient master plot of shipwreck provided a literary language for their dislocation and uncertainty. Mentz identifies three paradigms that expose the cultural meanings of shipwreck in historical and imaginative texts from the mid-sixteenth through the early eighteenth centuries.